2009
DOI: 10.1029/2008jc004863
|View full text |Cite
|
Sign up to set email alerts
|

A nested grid model of the Oregon Coastal Transition Zone: Simulations and comparisons with observations during the 2001 upwelling season

Abstract: [1] The Oregon Coastal Transition Zone (OCTZ) extends several hundred kilometers offshore where shelf flows interact with the northern California Current. A primitive-equation numerical ocean model is used to study the upwelling circulation in this region from 1 May to 1 November 2001. This OCTZ model obtains initial and boundary conditions from a larger-scale model of the California Current System and forcing from a regional atmospheric model product. The model results are compared with extensive in situ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 81 publications
5
34
0
Order By: Relevance
“…For these simulations, we adopt the nested grid model configuration for the Oregon Coastal Transition Zone (OCTZ) implemented by Springer et al (2009), who studied the upwelling circulation in the OCTZ region during summer 2001, and showed that this model reproduces relatively realistic OCTZ circulation features including shelf flow over the Heceta Bank, coastal jet separation and eddy formation offshore of Cape Blanco, and jet and eddy evolution in the offshore region. Simulations with this model configuration represent the OCTZ more faithfully than the periodic-channel domain used in related studies by Oke et al (2002a,b,c), Kurapov et al (2005a,b), and Kim et al (2009).…”
Section: A Model Configurationmentioning
confidence: 99%
See 3 more Smart Citations
“…For these simulations, we adopt the nested grid model configuration for the Oregon Coastal Transition Zone (OCTZ) implemented by Springer et al (2009), who studied the upwelling circulation in the OCTZ region during summer 2001, and showed that this model reproduces relatively realistic OCTZ circulation features including shelf flow over the Heceta Bank, coastal jet separation and eddy formation offshore of Cape Blanco, and jet and eddy evolution in the offshore region. Simulations with this model configuration represent the OCTZ more faithfully than the periodic-channel domain used in related studies by Oke et al (2002a,b,c), Kurapov et al (2005a,b), and Kim et al (2009).…”
Section: A Model Configurationmentioning
confidence: 99%
“…For the basic-case simulation, the model configuration and surface forcing is the same as that used by Springer et al (2009). The ocean initial and boundary conditions were obtained from spatial interpolation of the NCOM-CCS output, with the initial conditions taken from day 120 and the boundary information linearly interpolated in time between twice-daily NCOM-CCS output files.…”
Section: Basic Casementioning
confidence: 99%
See 2 more Smart Citations
“…Subgrid turbulence is parameterized using the level 2.5 Mellor-Yamada scheme [Mellor and Yamada, 1982;Wijesekera et al, 2003]. Process-oriented studies and extensive model-data comparisons of summer circulation have been performed in a similar domain using ROMS at the 3 km horizontal resolution [Springer et al, 2009;Kim et al, 2009;Koch et al, 2010]. Since variational DA requires repeated runs of the TL and ADJ codes, its computational cost can be on the order of 10-100 times as large as that of the forward nonlinear model run.…”
Section: Introductionmentioning
confidence: 99%